Life Skills Counseling within Local Culture-Based Schools Improves Muslim Students’ Self-Acceptance - Syahril Syahril; Sitti Riadil Janna; Bau Ratu; Kushan Indika Rathnasekara (Pamomong: Journal of Islamic Educational Counseling, 2025)
Many Muslim students in Southeast Asia struggle with self-acceptance, especially around body image with adverse implications for well-being. This study evaluated a culturally attuned life-skills counseling program in an Islamic higher-education setting. Using a quasi-experimental nonequivalent pretest–posttest control design at the State Islamic Institute (IAIN) Bone, Indonesia, 24 undergraduates with low self-acceptance were assigned to experiment group and control group. The intervention followed the DASIE sequence and integrated bibliotherapy and self-talk framed by Islamic virtues (muḥāsabah, shukr, riḍā) and local norms (adab, musyawarah). Self-acceptance was measured with the Husna & Fatonah scale (α=.961). Mann–Whitney analysis showed a significant post-intervention advantage for the counseling group (p=.001) with a large effect, indicating educationally meaningful gains. Mechanisms likely included identification with culturally relevant narratives and practice of faith-consistent self-evaluation. Findings support embedding faith-aligned, skills-based counseling within guidance services and training counselors in religiously attuned cognitive-behavioral methods across Islamic and local culture-based schools. Interpretation is qualified by a small, single-site, quasi-experimental design. Future multi-site randomized studies with longitudinal follow-up should test durability and examine mediators (e.g., self-compassion, perceived unconditional positive regard) and moderators (e.g., gender, socioeconomic status, religious commitment).